Risk assessment of venous thrombosis in families with known hereditary thrombophilia: the MARseilles‐NImes prediction model. (February 2014) - Cohen, W.; Castelli, C.; Suchon, P.; Bouvet, S.; Aillaud, M. F.; Brunet, D.; Barthet, M. C.; Alessi, M. C.; Trégouët, D. A.; Morange, P. E.
Summary Background Although predicting the risk of venous thrombosis (VT) in an individual from a family with inherited thrombophilia is of major importance, it is often not feasible. Objectives To develop a simple risk assessment model that improves prediction of the risk of VT for individuals of families with inherited thrombophilia. Patients/methods 1201 relatives from 430 families with inherited thrombophilia (deficiencies of antithrombin, protein C or protein S, and the factor V Leiden and F2 20210A mutations) were recruited at the referral center for thrombophilia in Marseilles, France, from 1986 to 2008. One hundred and twenty‐two individuals had a personal history of VT. Sixteen preselected clinical and laboratory variables were used to derive the VT risk score. Results The scores based on the 16 variables and on the five most strongly associated variables performed similarly (areas under receiver operating characteristic curves of 0.85 and 0.83, respectively). For the five‐variable score, named the MARNI score, derived from family history score of VT, von Willebrand factor antigen levels, age, severity of thrombophilia, and FGG rs2066865, the risk of VT ranged from 0.2% for individuals with a score of 0 (n = 186) to > 70% for individuals with a score of ≥ 7 (n = 27). The model was validated with an internal bootstrap method. Conclusions With the use of a simple scoring system, assessment of the risk of VT in subjects from families with inherited thrombophilia can be greatly improved. External validation is now needed to replicate these findings.